Use of recreational activity as one of the methods for treating urinary incontinence - Gabriela Kołodyńska; Adrian Sieroń (Kazimierz Wielki University, 2018)
Urinary incontinence (UI) is characterized by an involuntary leakage of urine due to bladder dysfunction of the locking mechanism and is an important social problem. It is estimated that in Poland this disease affects over 5 million people. According to recent data UI affects women twice as often. This condition occurs in about 25% of women of childbearing age and up 50% in postmenopausal women. In most cases, patients suffer from a form of stress urinary incontinence (SUI), which is a cause of lowering the interfacial tension perineal muscle, fascia, pelvic floor, and the loosening of connective tissue. Other, less common types of urinary incontinence include urge incontinence and overflow incontinence. Frequently it diagnosed as mixed forms of incontinence. The main role in the treatment of urinary incontinence should detach conservative treatment. Patients taking physical activity significantly speeds up the treatment of urinary incontinence. After the therapy and only through physical activity it is able to sustain the effects of treatment and to enjoy life free from symptoms of NTM.